Reading Philippine Science Fiction through science and technology studies the space race and authoritarian modernity in Gregorio Brillantes's" The Apollo Centennial" - Chua, Ethan; Chua, Scott Lee (2023)
We propose that analyses of Philippine science fiction can meaningfully contribute to the growing intersections between Philippine studies and science and technology studies. We argue that science fiction is not only a literary genre but also a mode of inquiry into our notions of progress and modernity. Through this lens, we examine Gregorio Brillantes's short story :The Apollo Centennial." Set in a future where the Ferdinand E. Marcos regime never ended. "The Apollo Centennial" demonstrates how state infrastructural interventions can discipline Filipino subjects according to the dictates of an authoritarian techno-future. Nevertheless , the short story also gesture to the emancipatory potential of alternative linguistic and sensory modes through which state subjects might imagine other futures that defy narrative sequestration.
Keywords: Marcos, Ferdinand E. -- Politician; Philippine literature; Philippine science fiction; Science fiction; Authoritarianism; Infrastructure